(3GdJYdje hGdbQhV GdCLfHjI (B/s - (3GdeJHhdj, UdGM GdOjfs ((3GdEScfOQjI(B: s (3OGQ GdhaGA(B, s, 2003)
(3eTcdI JGdHMK hCgejI OQGSJgG,eUGOQ GdJehjd GdCLfHj ddJYdje GdeUQj,GdeYhfI GdCeQjcjI dbWGY GdJYdje GdeUQj,feGPL ddbQhV hGdeYhfGJ GdCLfHjI GdehLgI Edi bWGY GdJYdje GdeUQj Ydi GdeSJhi GdKfGFj hGdeJYOO GdCWQGa eJeKdG aj bQhV(B((3GdHfc GdOhdj hHfc GdJfejI GdCaQjbj hHYV GdgjFGJ GdJGHYI ddCee GdeJMOI,GdOQGSI GdejOGfjI(B((3ELQGAGJgG(B-(3fJGFLgG(B-(3JMdjdgG(B)s
(3HjHdjhZQGajG U(B.289 (3;GdedGMb U(B.299 (3edNU GdHMK U(B.307s
Keywords: (3GdJYdje(B-(3eUQs